2011
DOI: 10.1371/journal.pone.0026749
|View full text |Cite
|
Sign up to set email alerts
|

Biological Responses to Diesel Exhaust Particles (DEPs) Depend on the Physicochemical Properties of the DEPs

Abstract: Diesel exhaust particles (DEPs) are the main components of ambient particulate materials, including polyaromatic hydrocarbons (PAHs), n-PAHs, heavy metals, and gaseous materials. Many epidemiological, clinical, and toxicological studies have shown that ambient particles, including DEPs, are associated with respiratory disorders, such as asthma, allergic rhinitis, and lung cancer. However, the relationship between the biological response to DEPs and their chemical composition remains unclear. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
2
24
2
Order By: Relevance
“…In contrast to HDM, which is rapidly degraded, DEP or at least its carbon core persists within phagocytic cells for weeks 25 . We assessed how long DEP persisted in lungs following a single exposure of DEP and found numerous DEP positive cells in the lungs 3 months later.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast to HDM, which is rapidly degraded, DEP or at least its carbon core persists within phagocytic cells for weeks 25 . We assessed how long DEP persisted in lungs following a single exposure of DEP and found numerous DEP positive cells in the lungs 3 months later.…”
Section: Resultsmentioning
confidence: 98%
“…Exposure to diesel fuel particles has been shown to increase allergic inflammation in both animal models and humans through increased local antigen-specific immunoglobulin E and cytokine release (43-45). In addition, animal and in vitro models of BaP exposure have indicated increases in histamine production following exposure periods (46, 47). While histamine was deceased in our study, association with BaP level nonetheless suggests changes in metabolic pathways important to immune response.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 It has been proposed that when diesel-exhaust particles are engulfed by macrophages, a Th2-type inflammatory response is induced, whereas diesel-exhaust particles that are not engulfed produce a Th1-type inflammatory response. [35][36][37] High carbon dioxide concentrations in the environment increase both pollen production and the allergenicity of pollen. Indeed, Singer et al 38 showed that high concentrations of carbon dioxide enhanced the production of Amb a 1, an allergenic protein in ragweed pollen, while Ziska et al 39 reported that in urban locations where carbon dioxide concentrations are higher, ragweed produces greater amounts of pollen (which contains the Amb allergen) than it does in rural locations.…”
Section: Allergic Diseasesmentioning
confidence: 99%